Analysis of the available funds supporting marine activities in some key European Mediterranean countries - Gambino, Monica; Accadia, Paolo; Costantini, Marco; Gomei, Marina; Malvarosa, Loretta; Sabatella, Evelina Carmen; Sabatella, Rosaria Felicita (Frontiers in Research Metrics and Analytics, 2022)
The study presented in this article analyzed qualitative and quantitative data on the performance of the European Maritime and Fisheries Fund (EMFF) based on the information reported in the European Union (EU) List of Operations updated to December 2020. Each EMFF measure and type of financial support were divided into three broad categories of subsidies according to their main objectives and scope: capacity enhancing, beneficial, or ambiguous. Capacity enhancing is defined as funds that could incentive overcapacity or overfishing. Beneficial refers to subsidies that have a positive impact on fish stocks and the environment. Ambiguous subsidies correspond to funds that may lead to positive or negative impacts on the environment depending on how they are designed and implemented. The assessment revealed the asymmetric distribution of EMFF resources in the Mediterranean region. In the six member states investigated, EMFF support is concentrated on a limited number of more easily accessible measures from an administrative and financial point of view. Most of the allocated funds are classified as capacity enhancing; other frequently used measures are in the ambiguous category. Small-scale vessels using static gear and accounting for the largest part of the Mediterranean fleets received a negligible share of specific funds for promoting environmentally sustainable fisheries. Most investments are concentrated on larger trawlers to support the temporary cessation of fishing activities and scrapping operations. Further qualitative analysis based on the findings and recommendations of previous reports evaluating the use of EMFF as well as interviews with beneficiaries highlighted that complex administrative procedures and legal uncertainty in the interpretations of some articles of the EMFF regulations are the main reasons for the asymmetric performance of the EMFF measures. The dispersion of responsibilities among European, national and regional authorities, and an evident lack of coordination among them are the main shortcomings that were identified. The limited use of advance payments, the lack of capacity, and technical assistance and obstacles to accessing financial instruments have penalized most of the projects that are focused on innovation, diversification, and environmental sustainability.